The On-site economic value of soil erosion control - Rapera, Corazon L. (1999)
Using the productivity change approach, the on-site economic value of one ton of avoided soil loss in moderately degraded upland farms was estimated to range from P2,100 to P8,280 per ha per year, depending on the rate of fertilization for the alley crop. Severely drgraded farms showed a net economic value ranging from zero to P1,860 per ha per year. Results suggest that in severely degraded upland farms, soil erosion control alone does not increase crop yields. In such sites, erosion control must be accompanied by full fertilization regimes, at least up to such time when the soil's natural fertility had been restored or built.
Keywords: Soil conservation; Soil erosion